The Arabidopsis AtPP2CA Protein Phosphatase Inhibits the GORK K(+) Efflux Channel and Exerts a Dominant Suppressive Effect on Phosphomimetic-activating Mutations - Lefoulon, Cécile (J Biol Chem, 2016)
The regulation of the GORK (Guard Cell Outward Rectifying) Shaker channel mediating a massive K(+) efflux in Arabidopsis guard cells by the phosphatase AtPP2CA was investigated. Unlike the gork mutant, the atpp2ca mutants displayed a phenotype of reduced transpiration. We found that AtPP2CA interacts physically with GORK and inhibits GORK activity in Xenopus oocytes. Several amino acid substitutions in the AtPP2CA active site, including the dominant interfering G145D mutation, disrupted the GORK-AtPP2CA interaction, meaning that the native conformation of the AtPP2CA active site is required for the GORK-AtPP2CA interaction. Furthermore, two serines in the GORK ankyrin domain that mimic phosphorylation (Ser to Glu) or dephosphorylation (Ser to Ala) were mutated. Mutations mimicking phosphorylation led to a significant increase in GORK activity, whereas mutations mimicking dephosphorylation had no effect on GORK. In Xenopus oocytes, the interaction of AtPP2CA with “phosphorylated” or “dephosphorylated” GORK systematically led to inhibition of the channel to the same baseline level. Single-channel recordings indicated that the GORK S722E mutation increases the open probability of the channel in the absence, but not in the presence, of AtPP2CA. The dephosphorylation-independent inactivation mechanism of GORK by AtPP2CA is discussed in relation with well known conformational changes in animal Shaker-like channels that lead to channel opening and closing. In plants, PP2C activity would control the stomatal aperture by regulating both GORK and SLAC1, the two main channels required for stomatal closure.